Visual perception and appraisal of persons with impairments: a randomised controlled field experiment using photo elicitation - Reinhardt, Jan Dietrich; Ballert, Carolina Saskia; Fellinghauer, Bernd; Lötscher, Alexander; Gradinger, Felix; Hilfiker, Roger; Graf, Sibylle; Stucki, Gerold (Disability and rehabilitation, 2011)
Visual cues from persons with impairments may trigger stereotypical generalisations that lead to prejudice and discrimination. The main objective of this pilot study is to examine whether visual stimuli of impairment activate latent prejudice against disability and whether this connection can be counteracted with priming strategies. In a field experiment, participants were asked to rate photographs showing models with mental impairments, wheelchair users with paraplegia, and persons without any visible impairment. Participants should appraise the models with regard to several features (e.g. communicativeness, intelligence). One hundred participants rated 12 photo models yielding a total of 1183 observations. One group of participants was primed with a cover story introducing visual perception of impairment as the study's gist, while controls received neutral information. Photo models with mental impairments were rated lowest and models without visible impairment highest. In participants who did not have prior contacts with persons with impairments, priming led to a levelling of scores of models with and without impairment. Prior contacts with persons with impairments created similar effects as the priming. Unexpectedly, a pattern of converse double discrimination to the disadvantage of men with mental impairments was revealed. Signs of stereotypical processing of visual cues of impairment have been found in participants of the Swiss general population. Personal contact with persons with impairments as well as priming participants seems to reduce stereotyping.